Pengaruh Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Pelanggan Pada Hotel Mathilda - Petrus Adrian; Antonius Phillipus K.Gheta; Nunsio Handrian Meylano (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Today's business development is characterized by diverse competition in all sectors. This situation increasingly demands businesses to have appropriate strategies to meet sales volume targets. Given the increasingly dynamic development of technology, people are required to act quickly and precisely to stay competitive. Marketing is crucial in line with the increasing demands of society.This study aims to determine the effect of service quality and location on customer satisfaction at the Mathilda Hotel. Customer satisfaction is a crucial factor in the sustainability of the hotel business, therefore, service quality and location are aspects that must be taken seriously. This research method used a quantitative method, with data collection techniques through distributing questionnaires to Mathilda Hotel customers. Data analysis was conducted using validity tests, reliability tests, multiple linear regression, and hypothesis testing (t-tests and f-tests) to determine the effect of independent variables on the dependent variable.The results showed that service quality has a positive and significant effect on customer satisfaction, while location also has a positive and significant effect on customer satisfaction. Simultaneously, service quality and location have a significant effect on customer satisfaction at the Matilda Hotel. Thus, it can be concluded that improving the quality of excellent service and selecting a strategic location are important factors in increasing customer satisfaction and loyalty to Hotel Mathilda.